Teachers Research Perception, Competence and Work Performance: Basis for A Capability Building Plan (International Journal of Scientific Research and Management (IJSRM), 2023)
This study investigated and explored the research perception, competence and work performance of teachers which was made basis for a capability building plan. This study further examined the teachers’ level of research perception in the area of time, cost, and knowledge as well as the teachers’ level of competence in the area of ability to work under pressure, ability to communicate, and technology capability in relation to their work performance. With the use of a qualitative research approach and a sample size of 155 teachers’ the data of the research perception, competence and work performance of teachers were collected. The findings revealed that there are no significant differences in the level of research perception and competence when each area is grouped according to the variable of highest educational attainment, number of trainings attended and length of service. It also revealed that there are significant differences existed in the level of teachers work performance specifically in the variable of educational attainment and length of service. It also revealed that there is no significant relationship existed between the level of research perception of District Murcia II teachers and their work performance. And there is a significant relationship existed between the level of research competence of District Murcia II teachers and their work performance. A proposed capability building plan was made to address the problem of teachers in terms of their level perception and competence in action research writing.